Military Engagement : Influencing Armed Forces Worldwide to Support Democratic Transitions. - Blair, Dennis C. (Brookings Institution Press, 2013)
The response of an autocratic nation's armed forces is crucial to the outcome of democratization movements throughout the world. But how can military officers and defense officials in democratic nations persuade their counterparts in autocratic regimes to favor democratic transitions? Here, Admiral Dennis Blair confronts this hard-edged challenge with a primer on the factors that affect military behavior during democratic transitions. Military Engagement makes the strong case for why the armed forces of any country should favor democracy and why, contrary to conventional wisdo.